2014
DOI: 10.48550/arxiv.1408.1369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coulomb effect in Au+Au and Pb+Pb collisions as a function of collision energy

Abstract: The subtle differences between positive and negative pion spectra can used be used to study the nature of the nuclear interaction region in heavy-ion collisions. Several large acceptance heavy ion experiments at facilities ranging from SIS, the AGS, the SPS, to RHIC have measured mid-rapidity π + and π − spectra for central Au+Au or Pb+Pb collisions. From these spectra one can create pion ratios as a function of mt − m0, which are used to determine the Coulomb potential, VC , and the initial pion ratio, Ri, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…where the value of the a and b parameters, as well as the 𝜒 2 /𝑑𝑜𝑓 are given in The f2 and f3 functions seems to describe better the behavior of the Coulomb kick energy dependence, while the f1 functions fails to describe this dependence. The Coulomb kick decrease with the increase of the beam energy, showing that the Coulomb interaction is stronger at lower energies, as it has been already observed in other analyzes [18][19][20]. If the colliding nuclei are strongly stopped, the total charge stays for a sufficient time to affect the charged pions.…”
Section: Resultssupporting
confidence: 61%
“…where the value of the a and b parameters, as well as the 𝜒 2 /𝑑𝑜𝑓 are given in The f2 and f3 functions seems to describe better the behavior of the Coulomb kick energy dependence, while the f1 functions fails to describe this dependence. The Coulomb kick decrease with the increase of the beam energy, showing that the Coulomb interaction is stronger at lower energies, as it has been already observed in other analyzes [18][19][20]. If the colliding nuclei are strongly stopped, the total charge stays for a sufficient time to affect the charged pions.…”
Section: Resultssupporting
confidence: 61%
“…within a hadronic transport model allowing for different freeze-out times and loci depending on the charge and momentum of the pions. Here, we follow instead a more data-driven ansatz similar to the one applied in [14,10], where all pions are assumed to freezeout at the same time, and parameterize the attenuation of the electrostatic force by replacing V C with an effective potential V eff expressed as a function of the pion kinetic energy measure for the relative velocities of pions and protons, and integrating over the proton velocity distribution, the authors of [14] found…”
Section: Coulomb Field Acting On Charged Pionsmentioning
confidence: 99%
“…Note that this second factor has been omitted in previous work, e.g. in [14,10], and it is novel in our methodology.…”
Section: Coulomb Field Acting On Charged Pionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9]. This prediction has sparked interest in the community, especially in light of the BES-II and its Fixed Target Program [24,25], which is intended to provide larger statistics and reach lower collision energies.…”
Section: Introductionmentioning
confidence: 99%